Development and Validation of a Novel Adult Spinal Deformity Surgical Invasiveness Score: Analysis of 464 Patients. Issue 6 (6th June 2017) - Neuman, Brian J; Ailon, Tamir; Scheer, Justin K; Klineberg, Eric; Sciubba, Daniel M; Jain, Amit; Zebala, Lukas P; Passias, Peter G; Daniels, Alan H; Burton, Douglas C; Protopsaltis, Themi S; Hamilton, D Kojo; et al.
Abstract: BACKGROUND: A surgical invasiveness index (SII) has been validated in general spine procedures but not adult spinal deformity (ASD). OBJECTIVE: To assess the ability of the SII to determine the invasiveness of ASD surgery and to create and validate a novel ASD index incorporating deformity-specific factors, which could serve as a standardized metric to compare outcomes and risk stratification of different ASD procedures for a given deformity. METHODS: Four hundred sixty-four patients who underwent ASD surgery between 2009 and 2012 were identified in 2 multicenter prospective registries. Multivariable models of estimated blood loss (EBL) and operative time were created using deformity-specific factors. Beta coefficients derived from these models were used to attribute points to each component. Scoring was iteratively refined to determine the R 2 value of multivariate models of EBL and operative time using adult spinal deformity-surgical (ASD-S) as an independent variable. Similarly, we determined weighting of postoperative changes in radiographical parameters, which were incorporated into another index (adult spinal deformity-surgical and radiographical [ASD-SR]). The ability of these models to predict surgical invasiveness was assessed in a validation cohort. RESULTS: Each index was a significant, independent predictor of EBL and operative time ( P < .001). On multivariate analysis, ASD-S and ASD-SR explained more variability in EBL and operative time than did the SII ( P < .001). The ASD-SR explained 21% of the variation in EBL and 10% of the variation in operative time, whereas the SII explained 17% and 3.2%, respectively. CONCLUSION: The ASD-SR, which incorporates deformity-specific components, more accurately predicts the magnitude of ASD surgery than does the SII.